PERAN DINAS KESEHATAN DALAM PENANGGULANGAN HIV/AIDS DI KABUPATEN SUMEDANG - Irma Hermayanty; Yuliyanti (Journal Of Regional Public Administration (JRPA), 2020)
This study aims to analyze the problem of the role of the health office, obstacles, and efforts to overcome obstacles in the prevention of HIV / AIDS in Sumedang Regency. The research method used is descriptive research using a qualitative analysis study approach. The sampling technique used was purposive sampling. With research informants namely the Secretary, the Head of Disease Prevention and Control, the Head of the Prevention and Control Section of Communicable Diseases, the Chairman of the Aids Prevention Commission in Sumedang Regency, and the Chairman of Citizens Care for Aids in Sumedang Regency. Data collection techniques using data analysis model Miles and Huberman with the steps: Data reduction, data presentation, Concultion Drawing / Verification, and Triangulation. Based on the results of the study, it was concluded that the health office had played a role in the prevention and control of HIV / AIDS, but it was still lacking in optimizing the role and support of the community, especially key populations who according to informants were not willing to carry out the proper examination or treatment. There are some suggestions from the author that can be used as references and recommendations to support the smooth role of the health office in HIV / AIDS prevention, namely by carrying out joint records with each of the cross-sectors regarding the development of activities and obstacles in the effort to combat HIV, so that later evaluations can be carried out related to tasks. and responsibilities of each across sectors. Then disseminate information using more creative media, one of which is using film media or leaflets.